2007
DOI: 10.1590/s0103-64402007000400013
|View full text |Cite
|
Sign up to set email alerts
|

Burning mouth syndrome: clinical profile of Brazilian patients and oral carriage of candida species

Abstract: Burning mouth syndrome (BMS) is a complex disease of unknown cause. It is characterized by a burning sensation in the oral mucosa, notwithstanding its clinical normal aspect. BMS is particularly seen in postmenopausal women. The purpose of this study was to investigate this syndrome on a clinical basis and, in addition, to analyze its possible relation to the frequency of Candida species. Thirty-one patients (28 women and 3 men; 13 Caucasians and 18 non-Caucasians; mean age = 61.3, range 30-85 years) were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 17 publications
(21 reference statements)
8
29
0
7
Order By: Relevance
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 89%
“…This study also confirmed the associated symptoms by both groups, i.e., the main symptom in one group appears as an associated symptom in the other group, and vice-versa (4,7,8,15,23,24) . The diversity of symptoms found and associated to the main symptoms -burning sensation and dry mouth -probably makes it difficult to discover the cause, which, as a consequence, results in various treatments (14,18,19,23) .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations